1999
DOI: 10.1515/znc-1999-1105
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids as Chemotaxonomic Markers for Erythroxylum ulei

Abstract: Leaf extracts of Erythroxylum ulei O. E. Schulz, produced six O-conjugated flavonoids. Three of the flavonoid aglycones were isoflavones, two were isoflavanones and the remainder a flavonol (quercetin). The major glycosides of these flavonols included mono-and dirham-nosides, mono-glucosides and galactosides with either 3̕ 4̕, or 7 linkage or a combination thereof. The two isoflavanones, in addition to being glycosylated, possessed a methyl group at position 2 of the C-ring. These flavonoids may be used as che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…truxillense and E. coca var. ipadu (from Colombia, South America); Johnson et al, 1997Johnson et al, , 1998Johnson et al, , 2002Johnson et al, , 2003, as well as the previous work of Bohm et al, 1981] kaempferol was found. However, E. ulei and E. australe, with similar arrays of flavonoids, both lacked the presence of kaempferol (Johnson and Schmidt, 1999).…”
Section: Leaf Flavonoid Chemistrymentioning
confidence: 68%
See 4 more Smart Citations
“…truxillense and E. coca var. ipadu (from Colombia, South America); Johnson et al, 1997Johnson et al, , 1998Johnson et al, , 2002Johnson et al, , 2003, as well as the previous work of Bohm et al, 1981] kaempferol was found. However, E. ulei and E. australe, with similar arrays of flavonoids, both lacked the presence of kaempferol (Johnson and Schmidt, 1999).…”
Section: Leaf Flavonoid Chemistrymentioning
confidence: 68%
“…ipadu (from Colombia, South America); Johnson et al, 1997Johnson et al, , 1998Johnson et al, , 2002Johnson et al, , 2003, as well as the previous work of Bohm et al, 1981] kaempferol was found. However, E. ulei and E. australe, with similar arrays of flavonoids, both lacked the presence of kaempferol (Johnson and Schmidt, 1999). We recognize that there are differences (quantitative) in flavonoid compositions of leaf tissue harvested from greenhouse, field and/or feral grown Erythroxylum, and that changes in their flavonoids will occur under different environmental conditions or when improperly stored.…”
Section: Leaf Flavonoid Chemistrymentioning
confidence: 68%
See 3 more Smart Citations